Attitude Towards Women Managers and Barriers in Their Career Advancement - Abd Aziz, Nurzarina (2001)
The objective of this study is to examine the attitude of the management level of a local commercial bank and its relationship with the causal attribution towards women managers' career advancement. A survey research was conducted with the participation of 70 employees (both male and female) from the management level of a local commercial bank. The sample of the respondents was based on simple random sampling. Structured questionnaires using the six-point Likert - type scales were used to measure the dependent and independent variables. The data collected were analyzed using the SPSSPC software The frequency distribution and measures of central tendency were employed in a descriptive analysis while the relationships between variables were analysed by using the independent t-test and one way ANOVA. The result reveals that more than half of the respondents (61.4%) have positive attitude towards women managers. The gender role of individuals also plays an important role in influencing the management level's attitude towards the women managers. Majority of the respondents identified that internal attributions for performance have a significant effects to the attitude towards women managers. The internal attributions for performance such as competence in doing a job and the ability in doing job were found to have a significant effect on the attitude towards women managers. Among the external factors investigated, only the perception that the job was easy job has been identified as a factor that affects the performance of women managers. Results of the ANOVA test show that qualification is the only demographic variable that has a significant influence on management's level attitude women managers. The study concludes that gender, internal attributions for performance and qualification contribute significantly to the management's attitude towards women managers. From the findings, it is recommended that a proactive action need to be taken to retain the women managers in the organization. A comprehensive study covering factors such as psychological and sociological factors are also recommended for future research to enrich the present literature